2009
DOI: 10.1159/000225979
|View full text |Cite
|
Sign up to set email alerts
|

The Hippocampus and Nucleus Accumbens as Potential Therapeutic Targets for Neurosurgical Intervention in Schizophrenia

Abstract: Schizophrenia is a chronic and disabling psychiatric illness that is often refractory to treatment. Psychotic symptoms (e.g. hallucinations and delusions) in schizophrenia are reliably correlated with excess dopamine levels in the striatum, and have more recently been related to excess metabolic activity in the hippocampus. Multiple lines of evidence suggest that aberrantly high hippocampal activity may, via hippocampal connections with the limbic basal ganglia, drive excessive dopamine release into the striat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 151 publications
3
64
0
3
Order By: Relevance
“…It is therefore suggested that the regulation of GABA A receptors by antipsychotics in the NAc might occur through regulating PKA signalling via D 2 -like receptors. In addition, since dysfunction of the NAc is involved in the positive symptoms of schizophrenia (Mikell et al, 2009) and the positive symptoms could be controlled by blocking D 2 receptors in NAc, our finding further suggests that PKA-GABA A signalling transmission is very likely to be involved in the therapeutic effects of antipsychotics (possibly in the positive symptoms of schizophrenia) (Fig. 5).…”
Section: Discussionmentioning
confidence: 54%
“…It is therefore suggested that the regulation of GABA A receptors by antipsychotics in the NAc might occur through regulating PKA signalling via D 2 -like receptors. In addition, since dysfunction of the NAc is involved in the positive symptoms of schizophrenia (Mikell et al, 2009) and the positive symptoms could be controlled by blocking D 2 receptors in NAc, our finding further suggests that PKA-GABA A signalling transmission is very likely to be involved in the therapeutic effects of antipsychotics (possibly in the positive symptoms of schizophrenia) (Fig. 5).…”
Section: Discussionmentioning
confidence: 54%
“…Building on the pathophysiologcal assumptions of Kapur, Mikell and colleagues suggested two subcortical regions (Mikell et al, 2009;Kapur, 2003) as putative target structures for DBS. Kapur et al (2005) had hypothesized that dopaminergic neurotransmission, which acts as a relevance detector in healthy subjects, e. g., in the reward system, misattributes salience to random stimuli in schizophrenia due to spontaneous and context-independent activity (Kapur, Mizrahi & Li, 2005).…”
Section: Second Approach: Modulation Of Dopaminergic Neurotransmissionmentioning
confidence: 99%
“…This dysfunction of the phasic dopamine release may lead to pathological salience and consecutively to positive symptoms. Based on this hypothesis and considering findings of dopaminergic hyperactivity of the anterior hippocampus (AHC) in psychosis, Mikell and colleagues identified the AHC and its efferences to the nucleus accumbens (NAcc) as putative target structures for DBS (Mikell et al, 2009). The authors considered functional lesioning of the AHC being safe and efficient in reducing dopaminergic hyperactivity in this brain region.…”
Section: Second Approach: Modulation Of Dopaminergic Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of newer target areas include the pedunculopontine nucleus (PPN, for Parkinsonian manifestations such as impaired gait and balance) [98] the internal capsule (for obsessive-compulsive disorder) [21] and Brodmann area 25 (for depression) [82]. Other disorders that are under trial for DBS are epilepsy [116], Tourette syndrome [1], cluster headache [74] and schizophrenia [86]. Thus, the future clinical applications of DBS are expected to include stimulation not just in the already identified targets, but also in a wide range of brain structures and nuclei, each target corresponding to a particular clinical manifestation or set of manifestations to be treated or reduced.…”
Section: Target Areas and Clinical Symptoms In Deep Brain Stimulationmentioning
confidence: 99%